Trends and burden of diabetes in patients with atrial fibrillation during 2007-2018: A Finnish nationwide cohort study - Teppo Konsta; Kouki Elis; Salmela Birgitta; Niskanen Leo; Jaakkola Jussi; Halminen Olli; Haukka Jari; Putaala Jukka; Linna Miika; Mustonen Pirjo; Hartikainen Juha; Airaksinen K. E. Juhani; et al. (ELSEVIER IRELAND LTD, 2025)
Aims: We assessed the temporal trends in the prevalence of diabetes and in its associations with outcomes among patients with atrial fibrillation (AF).
Methods: The registry-based FinACAF study covered all patients with incident AF in Finland between 2007 and 2018. Ischemic stroke (IS) and mortality rates were computed using Poisson regression model.
Results: We identified 229 565 patients (50.0% female; mean age 72.7 years; mean follow-up 4.0 years) patients with incident AF. The prevalence of diabetes increased steadily from 15.5% in 2007 to 26.3% in 2018. A decrease in IS and mortality rates was observed during the study period both in patients with and without diabetes. Diabetes was associated with IS and mortality (adjusted incidence rate ratios with 95% confidence intervals 1.22 (1.17-1.26) and 1.32 (1.29-1.34), respectively). The impact of diabetes on IS risk remained stable, while its effect on mortality increased slightly during the observation period.
Conclusions: The prevalence of diabetes has increased considerably among patients with AF between 2007 and 2018. There have been substantial improvements in the prognosis of AF patients with diabetes. However, diabetes remains a significant risk factor for IS and mortality in this patient population.